Problems and prospects for introducing the requirements of the standart Global G.A.P. by national agricultural producers - Slyva, Yuliia; Gumenyuk, Galina (My University, 2017)
A sufficient number of agricultural enterprises use equipment that does not meet technical standards for field work. First of all, it concerns the dosage of fertilizers and sprayers. The procedure of calibration and verification of this technique is almost not applied. Достатня кількість сільськогосподарських підприємств використовує обладнання, яке не відповідає технічні стандарти для польових робіт. Перш за все, це стосується дозування добрив і обприскувачі. Процедура калібрування і перевірки цієї техніки практично не існує застосовано.
Keywords: калібрування обладнання; сільськогосподарське обладнання; agricultural equipment; equipment calibration; кафедра експертизи харчових продуктів